(In)existências processuais - Gomes, Danilo Heber de Oliveira (2011)
Legal fact is all that matters to the legal world. If the law does not apply over the factual support, and juridicize , there is no legal fact, and also there is no legal effect, since only legal facts radiate legal effect. The study of (non)existence on legal process acts can be done based on a singular act or considering the whole procedure. The conclusion that an act does not exist does not mean that the whole procedure will also be nonexistent. The question of non-existence is connected to the lack of sufficient factual support. Being insufficient the factual support, indicates that there was no entry in the legal world. If deficient, the act went into the legal world, even though defective. The main debate of the dissertation is about to conclude if the procedural fact went into the legal world. To the existence of the process is necessary the existence of an initial act of the procedure, the act of suing, and the organ vested with jurisdiction. If there is a complaint to a court vested with jurisdiction, the process will enter into the legal world. The constitutional competence, the capability to be part, the citation and the conditions of action are not requirements to the existence of the process. The aptitude to the attorney is not a requirement to existence, but is linked to its effects only. Finally, the procedural way to recognize the inexistence of the act is declaratory action, because it is not possible to deconstruct, with the use of an annulment action, because by the non-existent nothing was made to deconstruct